Direct enantioseparation of mandelic acid by high‐performance liquid chromatography using a phenyl column precoated with a small amount of cyclodextrin additive in a mobile phase. Issue 7 (28th April 2020) - Watanabe, Yuri; Mikami, Ikko; Yamamoto, Atsushi; Aizawa, Sen‐ichi; Taga, Atsushi; Mochizuki, Naoki; Ishihara, Yoshimi; Kodama, Shuji
Abstract: Direct enantioseparation of mandelic acid by high‐performance liquid chromatography (HPLC) with a reversed phase column and a mobile phase containing a small amount of hydroxylpropyl‐β‐cyclodextrin (HP‐β‐CD) was studied as an efficient method for saving consumption of the CD additive. As a result, it was proposed that racemic mandelic acid can be analyzed with a phenyl column by using a mobile phase composed of 10 mM ammonium acetate buffer (pH 4.2) and 0.02% (w/v) HP‐β‐CD at a flow rate of 1.0 mL/min at 40°C after the passage of 10 mM ammonium acetate buffer (pH 4.2) containing 0.1% (w/v) HP‐β‐CD as a precoating mobile phase for 60 min. It is suggested that HP‐β‐CD is bound with a phenyl group on the surface of the stationary phase to allow a phenyl column to act as a transient chiral column, and injected mandelic acid can form the ternary complex with the adsorbed HP‐β‐CD. The longer retention time of D‐mandelic acid than the L‐isomer for HPLC can be explained from the higher stability of the HP‐β‐CD complex with D‐mandelic acid, which was confirmed by CE experiment with HP‐β‐CD as a selector. The efficiency of a phenyl column compared with other stationary phases was also discussed. Abstract :